2021
DOI: 10.1021/acsmaterialslett.1c00514
|View full text |Cite
|
Sign up to set email alerts
|

Micelle Formation inside Zeolites: A Critical Step in Zeolite Surfactant-Templating Observed by Raman Microspectroscopy

Abstract: Micelle formation inside faujasite (FAU) zeolite, a critical step in the introduction of mesoporosity in zeolites by surfactant templating, has been confirmed by both 13 C NMR and Raman spectroscopy. Here we provide unambiguous evidence of the incorporation of surfactant molecules inside zeolites during the first step of the surfactant-templating process followed by their self-assembly into micelles after hydrothermal treatment. The homogeneous presence of these micelles throughout zeoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It is noteworthy that the development of mesopore ordering is widely reported in FAU-type zeolites using CTAB at low pH conditions. [19,21,22] However, in the current work, the dissolution studies were carried out at higher pH to ensure the complete reorganization of zeolite precursor at different synthesis temperatures using different templates and bases. From the optimization studies, we found that the typical small size or linear PDAs such as…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is noteworthy that the development of mesopore ordering is widely reported in FAU-type zeolites using CTAB at low pH conditions. [19,21,22] However, in the current work, the dissolution studies were carried out at higher pH to ensure the complete reorganization of zeolite precursor at different synthesis temperatures using different templates and bases. From the optimization studies, we found that the typical small size or linear PDAs such as…”
Section: Resultsmentioning
confidence: 99%
“…Figures S1A and S1B depict the X‐ray diffraction (XRD) patterns of zeolites prepared by employing CTAB or organosilane‐dimethyloctadecyl‐(3‐trimethoxy‐silyl‐propyl)‐ammonium chloride as surfactants in the presence of a high concentration of ammonium hydroxide or urea. Small PDAs such as CTAB not only interact at the external surface of the crystal but also readily diffuse inside the zeolitic pores to prevent comprehensive dissolution for a complete reorganization [19] . Therefore, despite the formation of regional micelles, the mesopore ordering could be limited to shorter domains [22] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations